Self heat shock and gamma delta T-cell reactivity. - Rajasekar, R (1990)
We have investigated the effects of heat shock on T-cell induction and selection in vitro. We find that when cell preparations containing T lymphocytes are incubated for 30 min at 42 degrees C, a selective proliferation of gamma delta + T cells bearing the gamma delta T-cell antigen receptor follows. A greater enrichment of gamma delta + T cells is observed, upon preexposure to mycobacterial antigens in vivo. By comparing the effects of heat shock with that of mitogen or specific T-cell triggering by conventional antigens and by analyzing the gamma delta T-cell receptor genes expressed in cells that proliferate as a result of heat shock induction, we conclude that a subset of murine gamma delta T cells react to antigens on self cells in which a heat shock response was induced.